2019
DOI: 10.21203/rs.2.14194/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenotypic and genotypic profile of Enterobacteria resistant to beta-lactams

Abstract: Background: A serious emerging problem worldwide is increased antimicrobial resistance. Acquisition of coding genes for evasion methods of antimicrobial drug mechanisms characterizes acquired resistance. This phenomenon has been observed in several bacteria, including major species of Gram-negative bacteria such as the Enterobacteriaceae family. Among these, strains resistant to multiple classes of antibiotics were observed. Treatment for bacterial infections is performed with antibiotics and among the most us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…This is because antibiotic usage and infection control practices differ in various places (44). In the current study, the results revealed that the prevalence of ESBL genes bla CTX-M gene by using PCR in line with (45) they observed bla CTX-M β-lactamases genes in 46.7% of isolates ; (46) reported that the percentage of bla CTX-M was (65%) in Bacteria Isolated from Urinary Tract Infections in Bangladesh; (47) The presence of bla CTX-M enzyme among ESBLproducing in K.pneumoniae , in some extent near the study of (49) ,they stated that 24% of K. pneumonia was harbored the bla CTX-M gene in a study conducted in Iran ; (50) found that the prevalence of bla CTX-M in K. pneumonia in of North Sumatera isolates was 36.47 % ; Hihger percentage than our findings were reported by (51) in Al-Madenah Al-Monawwarah with a significant ratio (74.1%) and very low percentage around 2.7% conducted in health centers in Ouagadougou, Burkina Faso by (52) . Regarding E.coli isolates in the recent study ,the bla CTX-M percentage was compatible with Ahsan and Islam ,2019 ,they recorded that 24.2% of E.coli contained bla CTX-M ; (53) reported that the bla CTX-M in E.coil from UTI was 27% ; In a study conducted by (52) , that Approximately 39.6% E. coli harbored bla CTX-M. was recorded ; (54) reported very high rate of this gene in E.coli around 80.15% .P.aeruginosae in our study produced bla CTX-M gene in all groups in accordance with a study conducted by (55) , they recorded that 3.4% of P.aeruginosa was harbored bla CTX-M ; (56) in a research in the hospital of Makkah ,they stated that the frequencies of bla CTX-M in P.aeruginosae was only 10.7% ; In another study conducted by (57) ,they revealed that bla CTX-M was found in 17.5% of P. aeruginosae in urine samples ;Study conducted by (58) , incompatible with our result ,they revealed higher result around 31.7% of bla CTX-M in P.aeruginosae Bla TEM in the present study in accordance with several previous studies , in a study conducted for Clinical Isolates of Enterobacteriaceae in different Regions of Sudan by (59) ,they revealed that 61% were positive for bla TEM genes; (60) reported that bla TEM genes percentage was about 63% in Enterobacteriaceae among Patients in Ethiopia ;Other study conducted in Egypt on Enterobacteriaceae isolated from hospital acquired infections and community by (61) , they reported that bla TEM genes was about 73% in all isolates ; (62) in compatible with our results ,they record low percentage for bla TEM genes about 10.9 % in India .The recent study reported that bla TEM from all E.coli isolates is in agreement with (63) in Maiduguri reported bla TEM about (31.4%) ; Another study supported the findings was done by (52) found an overall 24.6% prevalence of TEM encoding genes in E. coli ; (64) They recorded that 38% of E coli isolates had the bla TEM gene ; …”
Section: Discussionsupporting
confidence: 72%
“…This is because antibiotic usage and infection control practices differ in various places (44). In the current study, the results revealed that the prevalence of ESBL genes bla CTX-M gene by using PCR in line with (45) they observed bla CTX-M β-lactamases genes in 46.7% of isolates ; (46) reported that the percentage of bla CTX-M was (65%) in Bacteria Isolated from Urinary Tract Infections in Bangladesh; (47) The presence of bla CTX-M enzyme among ESBLproducing in K.pneumoniae , in some extent near the study of (49) ,they stated that 24% of K. pneumonia was harbored the bla CTX-M gene in a study conducted in Iran ; (50) found that the prevalence of bla CTX-M in K. pneumonia in of North Sumatera isolates was 36.47 % ; Hihger percentage than our findings were reported by (51) in Al-Madenah Al-Monawwarah with a significant ratio (74.1%) and very low percentage around 2.7% conducted in health centers in Ouagadougou, Burkina Faso by (52) . Regarding E.coli isolates in the recent study ,the bla CTX-M percentage was compatible with Ahsan and Islam ,2019 ,they recorded that 24.2% of E.coli contained bla CTX-M ; (53) reported that the bla CTX-M in E.coil from UTI was 27% ; In a study conducted by (52) , that Approximately 39.6% E. coli harbored bla CTX-M. was recorded ; (54) reported very high rate of this gene in E.coli around 80.15% .P.aeruginosae in our study produced bla CTX-M gene in all groups in accordance with a study conducted by (55) , they recorded that 3.4% of P.aeruginosa was harbored bla CTX-M ; (56) in a research in the hospital of Makkah ,they stated that the frequencies of bla CTX-M in P.aeruginosae was only 10.7% ; In another study conducted by (57) ,they revealed that bla CTX-M was found in 17.5% of P. aeruginosae in urine samples ;Study conducted by (58) , incompatible with our result ,they revealed higher result around 31.7% of bla CTX-M in P.aeruginosae Bla TEM in the present study in accordance with several previous studies , in a study conducted for Clinical Isolates of Enterobacteriaceae in different Regions of Sudan by (59) ,they revealed that 61% were positive for bla TEM genes; (60) reported that bla TEM genes percentage was about 63% in Enterobacteriaceae among Patients in Ethiopia ;Other study conducted in Egypt on Enterobacteriaceae isolated from hospital acquired infections and community by (61) , they reported that bla TEM genes was about 73% in all isolates ; (62) in compatible with our results ,they record low percentage for bla TEM genes about 10.9 % in India .The recent study reported that bla TEM from all E.coli isolates is in agreement with (63) in Maiduguri reported bla TEM about (31.4%) ; Another study supported the findings was done by (52) found an overall 24.6% prevalence of TEM encoding genes in E. coli ; (64) They recorded that 38% of E coli isolates had the bla TEM gene ; …”
Section: Discussionsupporting
confidence: 72%
“…Observa-se que a massa dos frutos de P. schenckianum tem peso médio de 0,58 ± 0,013g com variação de 0,20 a 1,53 g, com mesocarpo medindo 0,80 ± 0,016 mm e uma composição interna de 3,57 ± 0,145 sementes por fruto, podendo apresentar frutos com 1 a 8 sementes (Tabela 1). A massa dos frutos encontrados nesse estudo é semelhante ao relatado por Santos et al (2014). expressem frutos de maior tamanho, peso alto e menor número de sementes por fruto (Rebouças, Gentil & Ferreira, 2018).…”
Section: Resultsunclassified
“…It is considered essential to maintain the blood clot for three-dimensional maintenance of the alveolus, as well as for the success of grafting techniques [20][21][22] . Following this principle, the blood clot needs to be kept in the tooth area that has been lost, to undergo a satisfactory bone repair, with a correct cicatrization of the edentulous alveolus 23,24 .…”
Section: Discussion:-mentioning
confidence: 99%